Identification of Biomarkers for Early Diagnosis of Crush Syndrome - Deniz Gezer; Semra Özkan (Galician Medical Journal)
Introduction. In the aftermath of natural disasters, hospitals often face a surge of patients with emergency injuries, posing significant challenges to emergency medical response systems. Effective biomarkers are essential for patient follow-up, treatment, and prognosis prediction. Studies to date have attempted to identify indicators of crush syndrome. With this study, we aimed to add to the growing body of literature on this subject.